Search for lepton-universality violation in B+→K+l+l−decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2019)
A measurement of the ratio of branching fractions of the decays B+→K+μ+μ− and B+→K+e+e− is presented. The proton-proton collision data used correspond to an integrated luminosity of 5.0 fb−1 recorded with the LHCb experiment at center-of-mass energies of 7, 8, and 13 TeV. For the dilepton mass-squared range 1.1<q2<6.0 GeV2/c4 the ratio of branching fractions is measured to be RK=0.846+0.060−0.054+0.016−0.014, where the first uncertainty is statistical and the second systematic. This is the most precise measurement of RK to date and is compatible with the standard model at the level of 2.5 standard deviations.